MMP and torque - duration profiles from u19 cyclists and WT cyclists - Bertron, Y.; Bowen, M.; Quiclet, J.-B.; Samozino, P.; Abel, A.; Pacot, A.; Hintzy, F.; Morel, B. (Journal of Science and Cycling, 2023)
Performance in cycling is often defines by the power produced by an athlete (i.e., power profile). Studies have tried to identify the differences between categories and levels. It has been showed that world tour cyclists have better qualities than the others. Moreover recently, it has been showed that power profile is mainly depend on the torque production capacities. The aim of our study was to investigate the torque at Mean Maximal Power - duration relationship by i) testing the fitting of the relative torque used in MMP from different durations ii) determine the differences between world tour cyclists (WT) and under nineteen cyclists (U19), because of the development strakes of this category. 17 u19 cyclists and 20 world tour participated in this study. Relative Power, cadence and relative torque data from one full season were used to determine the relative mean maximal power and relative mean torque relationships, for 10s, 1min, 2Min, 5min, 10min, 20min and 30min, and critical power was determined with the 3-parameter cp model. The goodness of fit was excellent (r² = .98 [.91-1). Significant differences were found from 5min to 30min and cp were found between the groups for relative power and relative torque data. No differences were found for the cadence. Torque duration relationship can be modelled and use to track performance of cyclists. Differences between world tour cyclists and under nineteen cyclists are mainly due to differences in torque capacities.